The one dimensional model for coarse particle around mining area in northern Sweden - Huang, Yi; Al-Ansari, Nadhir; Knutsson, Sven; Jia, Qi (Luleå tekniska universitet, Geoteknologi, 2012)
Computational model had been established to predict the coarse dust transport rate within the Malmberget mining area in northern Sweden. Matlab GUI designing had been introduced to enhance the computation process. Certain modification methods were developed in order to improve the accuracy of the model. Dust retention time was calculated to estimate the dust transport in the suspension form. Field calibration proves the code works fairly well for the coarse dust in the research area. Validerad; 2012; 20120601 (nadhir)